2013
DOI: 10.23986/afsci.8230
|View full text |Cite
|
Sign up to set email alerts
|

Trace element concentrations in the grain of wheat cultivars as affected by nitrogen fertilization

Abstract: Three winter wheat cultivars were grown under low-N and high-N fertilization rates over two growing seasons. In spite of smaller 1000-grain weight, the high-N fertilization produced higher grain yields as well as grain N and trace element concentrations in both growing seasons. Trace element increments with high-N rate averaged 14.0% for Fe, 9.2% for Zn, 19.7% for Mn, 13.2% for Cu, 15.1% for Ni, and 23.0% for Cd. Only Na concentration was unaffected by N fertilization, whereas Pb and Cr were below detection li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 18 publications
3
14
0
2
Order By: Relevance
“…The smaller the grain, the higher is the mass of the peripheral portion in the total mass of grain, which may contribute to higher concentrations of minerals in the grain as a whole. According to Svečnjak et al (), there is a weak correlation between the mass of 1000 grains and the concentrations of microelements, except in cultivars which differ significantly in the mass of 1000 grains, which is in line with our results. The concentration of mineral substances in wheat hull ash depends on ecological factors as well ( Terzioğlu et al, ), which may explain differences in Sr concentrations observed in different experimental years.…”
Section: Resultssupporting
confidence: 93%
“…The smaller the grain, the higher is the mass of the peripheral portion in the total mass of grain, which may contribute to higher concentrations of minerals in the grain as a whole. According to Svečnjak et al (), there is a weak correlation between the mass of 1000 grains and the concentrations of microelements, except in cultivars which differ significantly in the mass of 1000 grains, which is in line with our results. The concentration of mineral substances in wheat hull ash depends on ecological factors as well ( Terzioğlu et al, ), which may explain differences in Sr concentrations observed in different experimental years.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, we accept our third hypothesis regarding Mn in grain that the concentration of Mn in grain is similar or greater in inorganic N applied plots than in FYM or PV plots. Svecnjak et al [35] reported greater Mn in wheat grain with increased N rate, which is in line with our result. However, the mechanism involved in Mn uptake by N application is still not known.…”
Section: Total Micronutrient Accumulation In Wheat Grain and Strawsupporting
confidence: 93%
“…In contrast to a study of Warechowska (2009bWarechowska ( , 2009c, no statistically significant effect of the applied fertilization on the contents of Zn a studies do not support these Mn in grains of the wheat cultivars under analysis was found. According to Svečnjak et al (2013), grain yield is related to the content of basic micronutrients. Studies do not support these relationships (Table 6).…”
Section: Resultsmentioning
confidence: 99%